Sodobna gradnja z ilovico - Zbašnik-Senegačnik, Martina (AR. Arhitektura, raziskave, 2006)
Clay is a natural mineral building material that can be used throughout Europe, although the climatic differences are very varied. A large share of the buildings, especially of the housing stock that was built in the past from clay and clay derivatives, is still in use after several centuries and offers very pleasant living conditions. During the 70s of the last century building with clay almost vanished completely from Europe. It blossomed again after 1984, first in France and soon afterwards in Germany and elsewhere. The building material, used for several millennia to build homes, has returned, this time with an ecological denominator. Despite severe prejudice clay buildings are being built in ecologically conscious countries by using modernised traditional techniques In Europe, three techniques are being applied for building with clay: packed clay, clay bricks and a combination of timber and clay materials. The article describes clay, which complies with contemporary physical, functional design and construction demands. The main properties of the material and laboratory tests, needed before the clay material and the building technique are chosen, are shown. The article also presents some projects undertaken in Europe that prove the hypothesis about the suitability of the material for building.
Keywords: gradbeni materiali; ilovica; tehnologija gradnje